How to reduce Money Politics Practices in the 2019 Legislative Election through Education Politic - Al Yakin, Ahmad; Latief, Abdul; Wafie, Abdul; Dominggus, Ernawati (International Journal of Education Research and Development, 2022)
This research is motivated by problems regarding sociological behavior in the Mamasa village in the 2019 legislative elections which were indicated by money politics. The purpose of this study is to describe the factors that influence money politics in the 2019 legislative elections in Mamasa district. This study uses qualitative descriptive study design approach in a case study. Subjects of this study are representative of the communities involved with the politics of money on legislative elections 2019 in Mamasa district. The instruments used in this research were interviews and questionnaires. Data analysis was carried out qualitatively, namely data reduction, data presentation and conclusions. Based on the survey results revealed that the main factors of the cause of the money politics was low knowledge of the community about the political education greatly affects the occurrence of money politics in the Mamasa village. The influence of money politics was very significant in determining the participation of the Mamasa society for the PILKADA (regional election) in 2019.   Keywords: Money Politics, Election, Practices and Legislative Factors 2019.